The Renaissance explorers : with history projects for kids - Klepeis, Alicia, 1971- (Renaissance for kids., 2018)
Profiles five famous Renaissance-era explorers--Niccolò de' Conti, who traveled though South and Southeast Asia; Bartolomeu Dias, the first European to sail around the tip of Africa; Vasco da Gama, the first to sail directly from Europe to India; Pêro da Covilhã, who carried out secret diplomatic missions; and Ferdinand Magellan, the first European to cross the Pacific Ocean. Includes fast facts, timelines, side bars, maps, illustrations, and student projects.